Terapia intensiva com finger kazoo em professoras disfônicas com e sem afecções laríngeas ensaio clínico controlado e randomizado - Christmann, Mara Keli (2015)
Aim: verifying acoustic vocal, auditory-perceptive, videolaryngostroboscopic, aerodynamic measures, vocal sensations, quality of life and symptoms of anxiety and depression in dysphonic teachers of two groups before and after a brief and intensive therapy program with finger kazoo technique, comparing to their control groups, and comparing the study groups between themselves. Methods: Blinded randomized and controlled clinical trial. We carried out vocal acoustic analysis, perceptual analysis (by three speech therapists) and videolaryngostroboscopy analysis (by three otolaryngologists), evaluations of maximum phonation, of sound pressure level and were applied questionnaires in two study groups (one without structural alteration of the vocal folds, involving 15 subjects, and other with structural alteration of the vocal folds, in which nine subjects participated), before and after the therapy, and in two control groups (without structural alteration of the vocal folds involving nine subjects and structural alteration of the vocal folds involving eight subjects) who did not undergo therapy, but performed the evaluations in the same periods. Results: significant reduction in harmonic-noise ratio in the study group with alteration after therapy. When the study group without alteration is compared with its control group, we notice a significant decrease in jitter, shimmer and voiceless segments in favor of the study group. A significant reduction in dysphonia, hoarseness, breathiness and tension levels was verified, as well as a lower incidence of triangular slit - level II - and higher amplitude of vibration of the vocal folds in the study group with alteration. Besides there was a significant reduction in the maximum phonation time of /e/ in the study group without alteration and a significant reduction of the maximum sound pressure level in the study group with alteration. The Vocal Tract Discomfort Scale, the Profile of Participation in Voice Activity and the Vocal Symptoms Scale showed significant improvement in both study groups, with greater results in the study group with alteration. The negative vocal sensations reduced significantly in the study group without alteration. In the Quality of Life and Voice Protocol, there were similar significant improvements in both study groups. Anxiety symptoms improved significantly in the study group with alteration and the symptoms of depression improved significantly in the control groups with and study group without alteration. Conclusion: The brief and intensive care with finger kazoo provided voice, glottal closure, amplitude of vibration of the vocal folds improvements, improvement in sensations, quality of life and symptoms of anxiety and depression in dysphonic teachers with and without structural alteration of the vocal folds. Besides it provided a reduction of hyperfunction. Improvements were most evident in teachers without without alteration of the vocal folds.